Literature Review: The Relationship between Optimism and Psychological Well-being in Fresh Graduate Students Who Are Looking for Work - Nabillah, Jihan Luthfi; Saputra, Raihan; Evan Saputra; Satriawan, Nofri (Socrates: Journal of Education, Philosophy and Psychology, 2024)
The purpose of this study is to investigate the connection between psychological health and optimism in recent graduate students seeking employment. Especially in light of the current state of the economy and the fierce competition for jobs, optimism is seen as a critical component that can impact someone's mental health. This study makes use of literature analysis or library research. The study's findings demonstrate a strong positive correlation between optimism and psychological well-being, with people feeling more psychologically well-off when they had higher levels of optimism. These results highlight how crucial it is to cultivate optimism in order to enhance psychological wellbeing when making the shift to the working world. The ramifications of this study's findings can be utilised to create interventions and support systems for recently graduated students seeking employment that are more successful